Hyperreality to Misery: Migrant’s Worker’s Life in Hossine’s Me Migrant Selected Poems - Zahra, Nesa Fiikhtiyaril; Rositama , Whida (Faculty of Language and Literature, University of Surakarta, 2024)
In this increasingly sophisticated era, people have to fulfil many financial needs. Many people are trapped in poverty and finally decide to work abroad to become migrant workers. This happens because a person's expectations for working abroad are very high, namely a large salary. This research aims to explain that by becoming a migrant worker, many substances must be sacrificed, and the researchers want to inspire the public so that they are not influenced by the hyperreality of the existing media. This research uses a qualitative descriptive approach with hyperreality theory. Then the data source is Five Me Migrant Works by Md Mukul Hossine. The figurative language includes metaphor, personification, hyperbole, imagery, and symbolism. The research results show that the author talks about feelings of sadness, despair, longing, and loss of family and social life. Migrant workers' hyperreality of high wages is not always commensurate with the suffering they experience.